The Influence of Digital Technology on English Language Learning in Secondary Schools: An In-Depth Analysis - Sudiani, Sudiani; Zuhdi, Herman (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This research aims to analyse the influence of digital technology on English language learning in secondary schools. With the rapid development of digital technology, the importance of mastering English as an international language has increased significantly. This study employs a quantitative method with a questionnaire distributed to 200 students and 50 teachers across several secondary schools in Jakarta. The results indicate that 75% of students feel that digital technology has enhanced their understanding of English, while 80% of teachers state that the use of technology in teaching makes the learning process more engaging. However, challenges such as the lack of training for teachers in using technology persist. This research is expected to provide recommendations for the development of a more effective curriculum and teaching methods. In an increasingly interconnected global context, proficiency in English has become one of the essential skills. Therefore, this research focuses on how digital technology can facilitate English language learning at the secondary school level. By leveraging technology, it is hoped that the learning process can become more interactive, engaging, and effective. Through in-depth analysis, this study will also identify the challenges faced in the integration of technology in education, as well as provide recommendations for improvement.